Efektivitas dan Kontribusi Pajak Daerah Terhadap Pendapatan Asli Daerah - Kusumadewi, Hermala; Supardi, Supardi; Andini, Shafira (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2023)
This study aims to determine the effectiveness and contribution of local taxes to local revenue in Klaten Regency in 2018-2022. The research method used is the descriptive and quantitative method. The results of this study indicate that the level of effectiveness of PAD and local taxes in the Klaten Regency is considered effective. That shows that the Klaten Regency government can realize regional original income well. In addition, the higher regional tax contributions are street lighting tax, land and building tax, and Land and Building Rights Acquisition Tax. Apart from that, local taxes that have the lowest contributions are entertainment tax, parking tax, and hotel tax.